Red book : pharmacy's fundamental reference. - Group of Authors (Montvale, N.J. : Thomson, 2008)
A source of pricing information on over 100,000 prescription drugs, OTC medicines, and reimbursable medical supplies. It includes interactions data and FDA approved molecular entities.
Keywords: Pharmacopoeias - United States; Drugs; Therapeutics; Medicines